2013
DOI: 10.1158/1078-0432.ccr-13-0558
|View full text |Cite
|
Sign up to set email alerts
|

Impact of c-MYC Protein Expression on Outcome of Patients with Early-Stage HER2+ Breast Cancer Treated with Adjuvant Trastuzumab NCCTG (Alliance) N9831

Abstract: Purpose This study investigated the association between tumor MYC protein expression and disease-free survival (DFS) of patients randomized to receive chemotherapy alone (Arm A) or chemotherapy with sequential (Arm B) or concurrent trastuzumab (Arm C) in the N9831 (Alliance) adjuvant HER2+ trastuzumab breast cancer trial. Patients/Methods This analysis included 1736 patients randomized to Arms A, B, and C on N9831. Nuclear MYC protein expression was determined in tissue microarray (TMA) sections containing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…Deregulation of MYC stability may be particularly relevant in amplified-HER2 breast cancer, in which MYC amplification occurs at a higher rate than other breast tumor subtypes, and coamplification of MYC and HER2 is associated with worse outcome than either amplification alone (25)(26)(27)(28). In addition, high nuclear staining for MYC protein was associated with HER2 positivity and lymph node-positive disease (29). These observations support the notion that there is cooperation between HER2 signaling and deregulated MYC.…”
Section: Introductionsupporting
confidence: 63%
“…Deregulation of MYC stability may be particularly relevant in amplified-HER2 breast cancer, in which MYC amplification occurs at a higher rate than other breast tumor subtypes, and coamplification of MYC and HER2 is associated with worse outcome than either amplification alone (25)(26)(27)(28). In addition, high nuclear staining for MYC protein was associated with HER2 positivity and lymph node-positive disease (29). These observations support the notion that there is cooperation between HER2 signaling and deregulated MYC.…”
Section: Introductionsupporting
confidence: 63%
“…Green et al, (2016) revealed that positive c-Myc protein expression (nuclear and/or cytoplasmic) in breast cancer was significantly associated with tumor grade, lymph node stage and histological tumor type (medullary like tumors), while no significant association with tumor size or presence of lymphovascular emboli. Dueck et al, (2013) revealed that positive c-Myc nuclear staining in breast cancer was associated with nodal positivity and large tumor size. In prostatic cancer, Zeng et al, (2015) revealed that nuclear staining was associated with T-stage and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Geisler et al, (2004) reported that patients with endometrial carcinoma displaying cytoplasmic expression without nuclear staining had a better survival than those displaying combined nuclear and cytoplasmic expression. Cytoplasmic expression in breast cancer had been shown to be correlated with increased survival in a study done by Dueck et al, (2013). Gong et al, (2017) proposed that cytoplasmic expression was associated with high risk stratification of mantle cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Their functional status relies on their maturation status. Immature tumor infiltrating DCs (TIDCs) support tolerance of cancer cells, while mature TIDCs assist cancer elimination (65). Phenotypically mature DCs acquire expression of MHC class II, CD80, CD83 and CD86, these latter markers being negative or low on immature DCs.…”
Section: Markers Per Immune Cell Type and Functionmentioning
confidence: 99%
“…Phenotypically mature DCs acquire expression of MHC class II, CD80, CD83 and CD86, these latter markers being negative or low on immature DCs. Recent data point to the presence of additional subtypes of semi-mature DCs with either functional (e.g., cytokine expression profile) or phenotypic disparity from the fully mature DCs, leading to the assumption that the initial dichotomous view of DCs as either immature/tolerogenic or mature/immunogenic may be obsolete (65). It has been suggested that DNRG expression by DCs is associated with an antitumor response while Foxp3 expression may be related to T cell tolerance (47).…”
Section: Markers Per Immune Cell Type and Functionmentioning
confidence: 99%